Dunaliella salina chitosan nanoparticles as a promising wound healing vehicles: In-vitro and in-vivo study - Farouk K. El-Baz; Abeer Salama; Sami I. Ali; Hadeer A. El-Hashemy (OpenNano, 2023)
Dunaliella salina, a green microalga, is among the main sources of bioactive β-carotene and zeaxanthin. Hence, it will be investigated for its antioxidant effectiveness in wound healing. The current study's objective is to create new chitosan nanoparticle loaded D. salina hexane: ethyl acetate extract (HEAE-CNPs) and methanol extract (ME-CNPs) to be used in accelerating wound healing in-vivo. Double emulsion technique was utilized to prepare the nanoparticles. The prepared HEAE-CNPs and ME-CNPs were examined for in-vitro release and in-vivo wound healing efficacy in Wistar rats. Results confirmed that D. salina hexane:ethyl acetate extract (HEAE) contains 19.167 mg/g β-carotene and 16.196 mg/g zeaxanthin, whereas the extract of methanol (ME) contains only small amounts of zeaxanthin 0.313 mg/g as quantified by HPLC. The D. salina loaded chitosan gel greatly slowed the total carotenoids release, according to the in-vitro release assays, in comparison with D. salina nanoparticle dispersion with a particle size in the nanorange. By decreasing factor alpha (TNF-α) of tumor necrosis and increasing vascular endothelial growth factor (VEGF) and collagen skin contents, both HEAE-CNPs and ME-CNPs demonstrated wound healing and regeneration.